A Cohort Study on the Immunogenicity and Safety of the Inactivated SARS-CoV-2 Vaccine (BBIBP-CorV) in Patients With Breast Cancer; Does Trastuzumab Interfere With the Outcome? - Joudi, Maryam; Moradi Binabaj, Maryam; Porouhan, Pejman; PeyroShabany, Babak; Tabasi, Mohsen; Fazilat-Panah, Danial; Khajeh, Mahtab; Mehrabian, Arezoo; Dehghani, Mansoureh; Welsh, James S.; Keykhosravi, Batol; Akbari Yazdi, Azam; et al. (Frontiers in Endocrinology, 2022)
Aim: To determine the efficacy and safety of inactivated SARS-CoV-2 vaccine (BBIBP-CorV) in patients with breast cancer. Methods: In this multi- institutional cohort study, a total of 160 breast cancer patients (mean age of 50.01±11.5 years old) were assessed for the SARS-CoV-2 Anti-Spike IgG and SARS-CoV2 Anti RBD IgG by ELISA after two doses of 0.5 mL inactivated, COVID-19 vaccine (BBIBP-CorV). All patients were followed up for three months for clinical COVID-19 infection based on either PCR results or imaging findings. Common Terminology Criteria for Adverse Events were used to assess the side effects. Results: The presence of SARS-CoV-2 anti-spike IgG, SARS-CoV2 anti-RBD IgG, or either of these antibodies was 85.7%, 87.4%, and 93.3%. The prevalence of COVID-19 infection after vaccination was 0.7%, 0% and 0% for the first, second and third months of the follow-up period. The most common local and systemic side-effects were injection site pain and fever which were presented in 22.3% and 24.3% of patients, respectively. Discussion: The inactivated SARS-CoV-2 vaccine (BBIBP-CorV) is a tolerable and effective method to prevent COVID-19.